Descriptions of a common belief in an 1813 Japanese beauty handbook regarding the influence of striped clothing on perceived body shape. (September 2022) - Miyazaki, Yuki; Ishibashi, Kentaro
"Clothes with horizontal (or vertical) stripes are perceived as wider and shorter (slimmer and taller)." This belief is common yet inconsistent with the Helmholtz illusion. It has often attracted attention from researchers of perception. Despite the controversy among empirical studies, it is persistently supported by the general public. This article explores the early appearance of this common belief in Japan in historical records. Consequently, we discovered the descriptions of the common belief in a Japanese beauty handbook titled " Miyako Fuzoku Kewai Den [Cosmetic manners and customs in Edo], " published in 1813. In Japan, this belief was not born in modern times. Instead, it was established over 200 years ago, when vertical striped patterns on clothes were popularized.